The rights of the notary honoress assembly approval on notary calls in the judicial process - Hery Zaenal Kurniawan; Made Warka; Slamet Suhartono; Krisnadi Nasution (Technium Social Sciences Journal, 2021)
This research is a normative legal research using primary and secondary legal sources. Paying attention to the condisions needed for a notary’s summons to be present in the judicial process is felt to be very important, becaus it’s an effort to obtain the truth regarding legal cases involving parties who need the services of a notary and also a notary himself related to the deed he made in his client transactions. The efforts of the Notary Honorary Council in order to guarantee the protection of the position of a Notary are increasingly seen in the provisions of Article 27 paragraph (2) of the Regulation of the Minister of Law and Human Rights Number 7 of 2016 concerning the Notary Honorary Council, which is formulated: “The Regional Notary Honorary Council can accompany Notaries in the examination process before the investigator”.